Sendai virus-mediated CFTR gene transfer to the airway epithelium. - Ferrari, S; Griesenbach, U; Iida, A; Farley, R; Wright, A; Zhu, J; Munkonge, F; Smith, SN; You, J; Ban, H; Inoue, M; Chan, M; et al. (2007)
The potential for gene therapy to be an effective treatment for cystic fibrosis has been hampered by the limited gene transfer efficiency of current vectors. We have shown that recombinant Sendai virus (SeV) is highly efficient in mediating gene transfer to differentiated airway epithelial cells, because of its capacity to overcome the intra- and extracellular barriers known to limit gene delivery. Here, we have identified a novel method to allow the cystic fibrosis transmembrane conductance regulator (CFTR) cDNA sequence to be inserted within SeV (SeV-CFTR). Following in vitro transduction with SeV-CFTR, a chloride-selective current was observed using whole-cell and single-channel patch-clamp techniques. SeV-CFTR administration to the nasal epithelium of cystic fibrosis (CF) mice (Cftr(G551D) and Cftr(tm1Unc)TgN(FABPCFTR)#Jaw mice) led to partial correction of the CF chloride transport defect. In addition, when compared to a SeV control vector, a higher degree of inflammation and epithelial damage was found in the nasal epithelium of mice treated with SeV-CFTR. Second-generation transmission-incompetent F-deleted SeV-CFTR led to similar correction of the CF chloride transport defect in vivo as first-generation transmission-competent vectors. Further modifications to the vector or the host may make it easier to translate these studies into clinical trials of cystic fibrosis.